Implementation of Differentiated Instruction in the Merdeka Curriculum to Enhance Critical and Creative Thinking Dimensions - Dona Dinda Pratiwi; Riyama Ambarwati; Fitri Adelia Puspa (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2026)
The diversity of students’ abilities, interests, and learning styles requires adaptive learning strategies, making differentiated instruction a relevant approach to explore in greater depth. This study aims to examine the implementation of differentiated instruction within the Merdeka Curriculum regarding the critical and creative thinking dimensions of the Pancasila Student Profile at SMP Negeri 1 Anak Ratu Aji.  Data collection was conducted through observation, in-depth interviews, Focus Group Discussions (FGDs), and documentation, with the research subjects being mathematics teachers and students. Data analysis utilized the General Inductive Analysis (GIA) technique with triangulation to ensure data validity. The research results indicate that teachers have implemented differentiated instruction by adapting content, processes, and products to students’ readiness, interests, and learning profiles, thereby enhancing the critical and creative thinking dimensions within the Pancasila student profile. This is evident in increased student engagement, the ability to articulate ideas, and creativity in completing tasks. However, implementation still faces challenges in the form of time constraints, teachers’ workloads, and variations in students’ abilities to understand diverse learning instructions. Therefore, teachers need to enhance their capacity in designing differentiation-based formative assessments; educational institutions can integrate differentiation training into in-service training programs; and further research can develop differentiation-based assessments of critical and creative thinking.